Correlation of serial high-sensitivity cardiac troponin t values to infarct mass determined by cardiac magnetic resonance imaging. (3rd May 2023) - Biener, M; Giannitsis, E; Hegenbarth, A; Mueller-Hennessen, M; Andre, F; Katus, H A; Frey, N; Salatzki, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: The extent of myocardial injury is strongly associated with adverse outcome after acute myocardial infarction (AMI). Contrast-enhanced magnetic resonance imaging (CE-MRI) is the preferred technique for myocardial imaging. Its use in daily clinical practise, however, is restricted due to limited availability and high costs. High-sensitivity cardiac troponin T (hs-cTnT) correlates well with the extent of myocardial injury and may therefore be a cost effective and widely available surrogate for the estimation of infarct size. Purpose: To validate correlations between CE-MRI infarct mass and hs-cTnT values at different time points in patients with confirmed AMI. Methods: Patients presenting with AMI and with available CE-MRI between January 1, 2018 and December 31, 2020 were included. Correlation coefficients between hs-cTnT on admission, after 24h, 48h, 72h, 96h and peak hs-cTnT values and CE-MRI infarct mass were calculated. Correlations between hs-cTnT and CE-MRI infarct mass were compared to those of a 3rd generation cTnT assay from a previously published study of our group. Results: 137 patients were included for the present analysis. Median CE-MRI infarct mass was 12, 5 g (95%CI: 9.8-16.2 g). Hs-cTnT values and infarct mass correlated well at all time points including admission (r=0.474, [95%CI: 0.331-0.560], p<0.0001), 24h (r=0.508, [95%CI: 0.370-0.625], p<0.0001), 48h (r=0.547, [95%CI: 0.404-0.664], p<0.0001), 72h (r=0.489, [95%CI: 0.320-0.628], p<0.0001), 96h (r=0.509, [95%CI: 0.330-0.653], p<0.001) including peak hs-cTnT values (r=0.547, [95%CI: 0.416-0.656], p<0.0001) and maximum absolute delta changes within 96h (r=0.507, [95%CI: 0.369-0.622], p<0.001). Correlations of the 3rd generation assay could be confirmed for hs-cTnT at all time points. A superior correlation with CE-MRI infarct mass was observed for hs-cTnT values on admission. Conclusions: Hs-cTnT values at different time points correlate well with CE-MRI infarct mass. Correlations of admission hs-cTnT values are superior to those of a 3rd generation assay.